Maddening the Academy: Mad Studies, Critical Methodologies and Militant Research in Mental Health - Cea Madrid, Juan Carlos; Castillo, Tatiana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2021)
This article develops a conceptual and historical approach to Mad Studies, an investigative tradition that recognizes Madness as a valid and significant experience to generate critical knowledge against psychiatric discourse. In this framework, experiences of “mad” knowledge production are described that question the claim of objectivity and neutrality of the biomedical model in Mental Health. In turn, the contributions of critical methodologies and the militant research approach are analyzed in recent debates around the articulation of theory and committed praxis. Finally, the place of MadStudies in the academic field is examined, the scope of this initiative in university education and the challenges to link research and activism in the contemporary scenario.